Manicare Upaya Pencegahan Cacingan dan Peningkatan Kesadaran Kebersihan Pada Anak Sekolah Dasar di Cimahi - Febrianti, Vina; Berutu, Astri Lafenia; Khairunissa, Tasya Salsabilla; Hasna, Natasya Aliatul; Nurkurnia, Isyfi; Naully, Patricia Gita; Nursidika, Perdina (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background: Helminth infections are common among elementary school children in areas with poor sanitation, often resulting in anemia, growth disorders, and weakened immunity. A lack of awareness about personal hygiene, particularly nail cleanliness, contributes significantly to this problem. Objective: This study aimed to evaluate the effectiveness of the Manicare program, an educational intervention designed to improve students’ awareness and practices regarding nail hygiene. Methods: . A quantitative experimental design was used, involving 76 students from SD Negeri Linggabudi, Cimahi, selected through purposive sampling based on the presence of long and dirty nails. Nail samples were examined in the laboratory before and after the Manicare intervention, and students’ awareness of nail hygiene was assessed through direct observation. Data were analyzed using the Chi-Square test Results: The results of the study of 309 students showed that before the intervention, 76 students (24.6%) had long and dirty nails, while 233 students (75.4%) had short and clean nails. After the four-week intervention, all students had short and clean nails (100%). Laboratory examinations revealed that 1 student (1.3%) tested positive for helminth eggs before the intervention, whereas post-intervention results showed no helminth eggs in the examined samples. Conclusion: the Manicare program effectively improved students’ nail hygiene and may reduce the risk of helminth infections. Regular implementation of this program could serve as an effective preventive measure among elementary school children.